Using AI to Generate Dynamic Honeypots and Fake Data Trails to Confuse Attackers (International Journal of Information and Electronics Engineering, 2023)
This study highlights how artificial intelligence, or AI, can be applied to cybersecurity using dynamic honeypots and auto-generating fake data trails. This seeks to  decrease threat detection, misdirection of attackers, and collection